The Permit Power Revisited: The Theory and Practice of Regulatory Permits in the Administrative State - Biber, Eric (2014)
Two decades ago, Professor Richard Epstein fired a shot at the administrative state that has gone largely unanswered in legal scholarship. His target was the permit power, under which legislatures prohibit a specified activity by statute and delegate to administrative agencies the discretionary power to authorize the activity under terms the agency mandates in a regulatory permit. Accurately describing the permit power as an enormous power in the state, Epstein bemoaned that it had received scant attention in the academic literature. He sought to fill that gap. Centered on the premise that the permit power represents a complete inversion of the proper distribution of power within a legal system, Epstein launched a scathing critique of regulatory permitting in operation, condemning it as a racket for administrative abuses and excesses. Epstein's assessment of the permit power was and remains accurate in three respects: it is vast in scope, it is ripe for administrative abuse, and it has been largely ignored in legal scholarship. The problem is that, beyond what he got right about the permit power, most of Epstein's critique was based on an incomplete caricature of permitting in theory and practice. This Article is the first to return comprehensively to the permit power since Epstein's critique, offering a deep account of the theory and practice of regulatory permits in the administrative state. This Article opens by defining the various types of regulatory permits and describing the scope of permitting in the regulatory state. From there it compares different permit design approaches and explores the advantages of general permits, including their ability to mitigate many of the concerns Epstein advanced. This Article then applies a theoretical model to environmental degradation problems and concludes that if certain conditions are met, general permits can effectively respond to many of the complex policy problems of the future. Finally, this Article adds to the scholarship initiated by Epstein by proposing a set of default rules and exceptions for permit design and suggesting how they apply to complex policy problems